Inhaled mannitol for non-cystic fibrosis bronchiectasis: a randomised, controlled trial. Issue 12 (21st September 2014) - Bilton, Diana; Tino, Gregory; Barker, Alan F; Chambers, Daniel C; De Soyza, Anthony; Dupont, Lieven J A; O'Dochartaigh, Conor; van Haren, Eric H J; Vidal, Luis Otero; Welte, Tobias; Fox, Howard G; Wu, Jian; et al.
Abstract : Rationale: Bronchiectasis is characterised by excessive production of mucus and pulmonary exacerbations. Inhaled osmotic agents may enhance mucociliary clearance, but few long-term clinical trials have been conducted. Objectives: To determine the impact of inhaled mannitol on exacerbation rates in patients with non-cystic fibrosis (CF) bronchiectasis. Secondary endpoints included time to first exacerbation, duration of exacerbations, antibiotic use for exacerbations and quality of life (QOL) (St George's Respiratory Questionnaire, SGRQ). Methods: Patients with non-CF bronchiectasis and a history of chronic excess production of sputum and ≥2 pulmonary exacerbations in the previous 12 months were randomised (1:1) to 52 weeks treatment with inhaled mannitol 400 mg or low-dose mannitol control twice a day. Patients were 18–85 years of age, baseline FEV1 ≥40% and ≤85% predicted and a baseline SGRQ score ≥30. Main results: 461 patients (233 in the mannitol and 228 in the control arm) were treated. Baseline demographics were similar in the two arms. The exacerbation rate was not significantly reduced on mannitol (rate ratio 0.92, p=0.31). However, time to first exacerbation was increased on mannitol (HR 0.78, p=0.022). SGRQ score was improved on mannitol compared with low-dose mannitol control (−2.4 units, p=0.046). Adverse events were similar between groups. Conclusions: Mannitol 400 mg inhaled twice daily for 12 months in patients with clinically significant bronchiectasis did not significantly reduce exacerbation rates. There were statistically significant improvements in time to first exacerbation and QOL. Mannitol therapy was safe and well tolerated. Trial registration number: NCT00669331.